Anti‐HIV‐1 Peptide Derivatives Based on the HIV‐1 Co‐receptor CXCR4. Issue 10 (23rd August 2013) - Hashimoto, Chie; Nomura, Wataru; Narumi, Tetsuo; Fujino, Masayuki; Tsutsumi, Hiroshi; Haseyama, Masaki; Yamamoto, Naoki; Murakami, Tsutomu; Tamamura, Hirokazu
Abstract The human immunodeficiency virus type 1 (HIV‐1) uses CD4 and the co‐receptor CCR5 or CXCR4 in the process of cell entry. The negatively charged extracellular domains of CXCR4 (CXCR4‐ED) interact with positive charges on the V3 loop of gp120, facilitating binding via electrostatic interactions. The presence of highly conserved positively charged residues in the V3 loop suggests that CXCR4‐ED‐derived inhibitors might be broadly effective inhibitors. Synthetic peptide derivatives were evaluated for anti‐HIV‐1 activity. The 39‐mer extracellular N‐terminal region (NT) was divided into three fragments with 10‐mer overlapping sites (N1–N3), and these linear peptides were synthesized. Peptide N1 contains Met 1–Asp 20 and shows significant anti‐HIV‐1 activity. Extracellular loops 1 and 2 (ECL1 and 2) were mimicked by cyclic peptides C1 and C2, which were synthesized by chemoselective cyclization. Cyclic peptides C1 and C2 show higher anti‐HIV‐1 activity than their linear peptide counterparts, L1 and L2. The cytotoxicities of C1 and C2 are lower than those of L1 and L2. These results indicate that Met 1–Asp 20 segments of the NT and cyclic peptides of ECL1 and ECL2 are potent anti‐HIV‐1 drug candidates.